Formation mechanism and regulation analysis of trumpet leaf in Ginkgo biloba L - Li, Xin-hui; Kang, Xiao-jing; Zhang, Xin-yue; Su, Li-ning; Bi, Xing; Wang, Rui-long; Xing, Shi-yan; Sun, Li-min (Frontiers in Plant Science, 2024)
Introduction The research on plant leaf morphology is of great significance for understanding the development and evolution of plant organ morphology. As a relict plant, the G. biloba leaf morphology typically exhibits bifoliate and peltate forms. However, throughout its long evolutionary history, Ginkgo leaves have undergone diverse changes. Methods This study focuses on the distinct “trumpet” leaves and normal fan-shaped leaves of G. biloba for analysis of their phenotypes, photosynthetic activity, anatomical observations, as well as transcriptomic and metabolomic analyses. Results The results showed that trumpet-shaped G. biloba leaves have fewer cells, significant morphological differences between dorsal and abaxial epidermal cells, leading to a significantly lower net photosynthetic rate. Additionally, this study found that endogenous plant hormones such as GA, auxin, and JA as well as metabolites such as flavonoids and phenolic acids play roles in the formation of trumpet-shaped G. biloba leaves. Moreover, the experiments revealed the regulatory mechanisms of various key biological processes and gene expressions in the trumpet-shaped leaves of G. biloba. Discussion Differences in the dorsal and abdominal cells of G. biloba leaves can cause the leaf to curl, thus reducing the overall photosynthetic efficiency of the leaves. However, the morphology of plant leaves is determined during the primordia leaf stage. In the early stages of leaf development, the shoot apical meristem (SAM) determines the developmental morphology of dicotyledonous plant leaves. This process involves the activity of multiple gene families and small RNAs. The establishment of leaf morphology is complexly regulated by various endogenous hormones, including the effect of auxin on cell walls. Additionally, changes in intracellular ion concentrations, such as fluctuations in Ca2+ concentration, also affect cell wall rigidity, thereby influencing leaf growth morphology.